Gene fusion characterisation of rare aggressive prostate cancer variants-adenosquamous carcinoma, pleomorphic giant-cell carcinoma, and sarcomatoid carcinoma: an analysis of 19 cases - Alhamar, Mohamed; Tudor Vladislav, I; Smith, Steven C; Gao, Yuan; Cheng, Liang; Favazza, Laura A; Alani, Ali M; Ittmann, Michael M; Riddle, Nicole D; Whiteley, Lisa J; Gupta, Nilesh S; Carskadon, Shannon; et al. (Histopathology, 2020)
AIMS: To evaluate the molecular underpinnings of the rare aggressive prostate cancer variants adenosquamous carcinoma, pleomorphic giant-cell carcinoma, and sarcomatoid carcinoma. METHODS AND RESULTS: We retrieved 19 tumours with one or more variant(s), and performed ERG immunohistochemistry, a next-generation sequencing assay targeting recurrent gene fusions, and fluorescence in-situ hybridisation (FISH) for ERG and BRAF. Divergent differentiation included: sarcomatoid carcinoma (n = 10), adenosquamous carcinoma (n = 7), and pleomorphic giant-cell carcinoma (n = 7). Five patients had more than one variant. Four had variants only in metastases. ERG rearrangement was detected in nine (47%, seven via sequencing, showing TMPRSS2-ERG fusions and one GRHL2-ERG fusion, and two via FISH, showing rearrangement via deletion). ERG was immunohistochemically positive in the adenocarcinoma in eight of nine (89%) patients, but was immunohistochemically positive in the variant in only five of nine patients (56%, typically decreased). One patient had a false-positive ERG immunohistochemical result in the sarcomatoid component despite a negative FISH result. Two (11%) harboured BRAF fusions (FAM131A-BRAF and SND1-BRAF). CONCLUSIONS: ERG fusions are present in these rare prostate cancer variants with a frequency close to that in conventional prostate cancer (9/19, 47%). ERG immunohistochemistry usually detects rearrangement in the adenocarcinoma, but is less sensitive for the variant histology, with weak to negative staining. Adenosquamous and sarcomatoid variants can, particularly, occur together. Molecular assessment may be an additional tool in selected cases to confirm the prostatic origin of unusual tumours. The presence of two BRAF rearrangements suggests that this gene fusion may be enriched in this setting, as RAF kinase fusions have been previously reported in 1-2% of prostate cancers.
Keywords: fúze genů; senioři nad 80 let; metastázy nádorů; Transcription Factors; genová přestavba; hybridizace in situ fluorescenční; Gene Rearrangement; Carcinoma, Renal Cell; Humans; lidé středního věku; Oncogene Proteins, Fusion; transkripční faktory; Aged, 80 and over; Middle Aged; karcinom z renálních buněk; In Situ Hybridization, Fluorescence; imunohistochemie; DNA-Binding Proteins; Carcinoma, Giant Cell; mužské pohlaví; Immunohistochemistry; Transcriptional Regulator ERG; vysoce účinné nukleotidové sekvenování; nádory prostaty; protoonkogenní proteiny B-raf; DNA vazebné proteiny; fúzní onkogenní proteiny; Neoplasm Metastasis; Prostatic Neoplasms; Serine Endopeptidases; Proto-Oncogene Proteins B-raf; Carcinoma, Adenosquamous; adenoskvamózní karcinom; lidé; serinové endopeptidasy; Gene Fusion; Aged; senioři; Male; obrovskobuněčný karcinom; High-Throughput Nucleotide Sequencing; transkripční regulátor ERG